Fuzzy number in determining the optimal solution of multiple input multiple output (MIMO) system - Maan, Normah; Ahmad, Tahir (2008)
It is known that many industrial applications had successfully used the concept of fuzzy number in order to solve their problems. Therefore in this paper, we provide the application of one dimensional fuzzy number and show when it is necessary that the employment of higher degree of fuzzy number should be considered. To achieve this, 2-dimensional fuzzy number concept, specifically pyramidal fuzzy number is discussed. The definition of pyramidal fuzzy number and its alpha-level set are also given. Both of the concepts are then employed in determining the optimal input parameters in the mass transfer process of a dynamical system. The numerical examples demonstrating that the method are reasonable and effective are also given. We conclude that this new technique gives a useful information and provides a faster tool for decision maker.